Moderasi Profitabilitas pada Pengaruh Makroekonomi dan Fundamental terhadap Nilai Perusahaan Consumer Cyclicals - Vedro Falensia; Elfiswandi .; Nike Apriyanti (CV. ITTC INDONESIA, 2026)
The global and domestic economic dynamics during the 2020-2024 period exerted significant pressure on the Consumer Cyclicals sector, which is sensitive to purchasing power, characterized by inflation fluctuations and changes in consumption behavior. This study aims to examine the effect of Inflation, Gross Domestic Product (GDP), Leverage, and Dividend Policy on Firm Value with Profitability as a moderating variable. The population in this study comprises Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The sampling method used was the Purposive Sampling technique, resulting in a sample of 36 companies with a total of 180 observations. Data collection techniques involved secondary data from financial reports, processed using EViews 12 software with the Random Effect Model estimation. The findings show that GDP has a significant negative effect and Leverage has a significant positive effect on Firm Value, while Inflation and Dividend Policy do not have a significant effect on Firm Value. Profitability is proven to moderate and strengthen the relationship between Dividend Policy and Firm Value, and able to moderate the relationship between Inflation and Firm Value but insignificantly, however, it is unable to moderate the effects of GDP and Leverage on Firm Value.